2014
DOI: 10.5398/medpet.2014.37.3.155
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol Hormone Concentration and Meat Quality of Beef Cattle Stunned by Captive Bolt Stun Gun before Slaughtering

Abstract: This study �as aimed to describe cortisol hormone concentration and meat �uality �hich �ere �as aimed to describe cortisol hormone concentration and meat �uality �hich �ere aimed to describe cortisol hormone concentration and meat �uality �hich �ere produced in beef cattle stunned with captive bolt stun gun before slaughtering. Blood and meat samples were taken from Brahman cross steers �n�� ���� in two abattoirs located in �est �ava and Banten. s �n�� ���� in two abattoirs located in �est �ava and Banten. �n�… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
2
1
Order By: Relevance
“…In particular, plasma cortisol levels showed a similar trend in all three steps of our experimental study and this mirrors the results described in traditionally slaughtered animals after stunning [ 8 ]. Conversely, the average plasma cortisol values observed in this study were lower than those reported in the literature [ 28 , 29 ]. The plasma dopamine values of the calves slaughtered by traditional method, detected in steps 1 and 2, were slightly higher than the values observed in the animals slaughtered by the Jewish religious rite.…”
Section: Discussioncontrasting
confidence: 98%
“…In particular, plasma cortisol levels showed a similar trend in all three steps of our experimental study and this mirrors the results described in traditionally slaughtered animals after stunning [ 8 ]. Conversely, the average plasma cortisol values observed in this study were lower than those reported in the literature [ 28 , 29 ]. The plasma dopamine values of the calves slaughtered by traditional method, detected in steps 1 and 2, were slightly higher than the values observed in the animals slaughtered by the Jewish religious rite.…”
Section: Discussioncontrasting
confidence: 98%
“…The lack of a head restraint results in a low SP accuracy, thus increasing the risk of stunning failure because the cattle head can still move freely to avoid stunning (Von Wenzlawowicz et al, 2012), causing the stunner-man to take longer time to perform the stunning. Poor handling when animals enter the restraining box and the time frame of the stunning action can have different effects on the psychological status of the animal in relation to stress-related hormone assessments (Khan et al, 2018. Maghfiroh et al, 2014Zulkifli et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Dokmanović et al [38] correlated different categories of animal stresses, meat quality, and carcass quality characteristics in pigs and found that cortisol affected the carcass quality. High cortisol values in beef cattle resulted in high pH but cooking loss values were still within the normal range [39]. After arrival at the slaughterhouse, two important factors that may affect the level of stress in pigs and consequently pork quality, are lairage time and handling procedure immediately prior to slaughter [40].…”
Section: Stress Factors That Affect Meat Qualitymentioning
confidence: 99%